## Simplifying the Expression (6m - 7) ⋅ 4

This expression involves the distributive property of multiplication. Let's break it down step-by-step to simplify it.

### Understanding the Distributive Property

The distributive property states that multiplying a sum by a number is the same as multiplying each addend in the sum by the number and then adding the products. Mathematically:

**a ⋅ (b + c) = (a ⋅ b) + (a ⋅ c)**

### Applying the Distributive Property

In our expression, (6m - 7) ⋅ 4, we have:

**a = 4****b = 6m****c = -7**

Applying the distributive property:

(6m - 7) ⋅ 4 = (4 ⋅ 6m) + (4 ⋅ -7)

### Simplifying the Expression

Now, we can perform the multiplication:

(4 ⋅ 6m) + (4 ⋅ -7) = **24m - 28**

### Final Result

Therefore, the simplified form of the expression (6m - 7) ⋅ 4 is **24m - 28**.